THE EFFECTIVENESS OF ETHNOMATEMATICS BASED LEARNING ON MATHEMATICS ABILITY OF ELEMENTARY SCHOOL STUDENTS: A META-ANALYIS STUDY - Endang Sulistyowati; Dona Ningrum Mawardi (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Mixing culture and mathematics can provide more meaningful mathematics learning so that abstractions of mathematical material can be more easily understood by students. However, previous studies investigating the effectiveness of implementing ethnomathematics-based learning in elementary schools showed mixed results. Therefore, this study aims to determine the effectiveness of ethnomathematics-based learning on the mathematics abilities of elementary school students using a meta-analysis approach. This study analyzed 13 effect sizes from 12 primary studies that met the inclusion criteria. The results of the analysis show that the application of ethnomathematics-based learning has a strong effect on the mathematics abilities of elementary school students when compared to traditional learning (g = 1.74; p <0.01). The results of the research based on the moderator variable showed that the effect of implementing ethnomathematics-based learning on the mathematics abilities of elementary school students differed according to the year of study (Qb = 10.22; p = 0.00), however, there was no difference based on the class level group (Qb = 1.98; p = 0.16) and sample size (Qb = 0.30; p = 0.58). It is hoped that the results of this study can become the basis for choosing a mathematics learning approach so that the quality of mathematics learning in elementary schools can be improved.